Meningkatkan Pengetahuan Masyarakat Pontang-Banten Terkait Kandungan Gizi Jamur Tiram Melalui Sosialisasi dan Pendampingan Pengolahan Jamur Tiram - Indah Juwita Sari; Desi Nur Eka Fitriana; Mila Ermila Hendriyani; Rida Oktorida Khastini; Tasya Alya Permata (Jurnal Pemberdayaan Masyarakat, 2023)
Pontang is one of the villages in Banten with a high potential for natural resources but unexplored potential for human resources. Continuous socialization and mentoring are one way to increase the potential and knowledge of the Pontang people. This activity aims to determine an increase in Pontang people's knowledge of oyster mushrooms' nutritional contents and their benefits in meeting food needs. The method used in this activity is a case study with questionnaires and interviews as instruments. This activity was started by giving questionnaires about the initial knowledge of oyster mushrooms' nutritional contents to 20 samples. After that, socialization and mentoring were carried out in oyster mushroom processing into oyster mushroom meatballs. Interviews related to participants' knowledge of the oyster mushrooms' nutritional contents were conducted at the end of the activity. This activity showed increased knowledge about the oyster mushrooms' nutritional contents and benefits and participants' satisfaction after socialization and mentoring in oyster mushroom processing. This activity initiated the participants to utilize oyster mushrooms as an alternative to meet their daily vegetable protein needs. In addition, this activity initiated the participants to explore entrepreneurial potential, such as innovation in processed oyster mushroom food.